Effects of occupant behavior on the energy performance of dwellings - Gülsu Ulukavak Harputlugil; Merve Bedir (A+BE: Architecture and the Built Environment)
Chapter 3 is a sensitivity analysis conducted using the actual heating behavior data of occupants in the OTB sample. The aim was to model heating behavior and heating energy consumption using Markov chains and Monte Carlo methods. Secondly we wanted to evaluate the robustness of energy consumption of a dwelling to heating behaviors such as thermostat, radiator and ventilation control, as well as presence. The results of this Chapter were compared to Guerra Santin’s work (2010), which analyzes the same data using correlation and regression analyses.